Le profonde ragioni di una crisi annunciata - Bernardini, Fulvio (GEOmedia, 2009)
The heavy reasons of an announced crisis De Agostini, an important player in the italian cartographic sector, recently came under severe financial pressure, jeopardising the future of it's employees. The mismanagement and wrong choice of policies in addition to the extreme changes occurred in the fundamental concepts of cartography, were the main cause of this downfall.